POSTMILENIALISME BERSYARAT: KRITIK TERHADAP ESKATOLOGI PREMILENIALISME DISPENSASIONAL DAN SEBUAH USULAN TERHADAP ESKATOLOGI PENTAKOSTA: CONDITIONAL POSTMILLENIALISM: CRITICISM OF THE ESCHATOLOGY OF DISPENSATIONAL PREMILENIALISM AND A PROPOSAL TO PENTECOSTAL ESCHATOLOGY - Jessica Layantara (Jurnal Teologi Amreta (ISSN: 2599-3100))
So far, Pentecostal eschatology has always been connected with dispensational premillennialist views. But if analyzed, there are actually many things in dispensational premillennialism that are incompatible with Pentecostal theology. This article will briefly explain the history of how Pentecostal eschatology can be influenced by dispensational premillennialism, as well as providing criticisms that prove that this view actually does not correspond essentially with Pentecostal teaching. This article will also try to propose a model of conditional postmillennialism, which is seen as more appropriate to become a framework of Pentecostal eschatology. === Selama ini eskatologi Pentakosta selalu dihubungkan dengan pandangan premilenialisme dispensasional. Namun jika dianalisa, sebenarnya banyak hal di dalam premilenialisme dispensasional yang tidak sesuai dengan teologi Pentakosta. Artikel ini akan menjelaskan secara singkat sejarah bagaimana eskatologi Pentakosta dapat dipengaruhi oleh premilenialisme dispensasional, serta memberikan kritik-kritik yang membuktikan bahwa pandangan tersebut sebenarnya tidak bersesuaian secara esensial dengan pengajaran Pentakosta. Artikel ini juga akan mencoba mengusulkan sebuah model eskatologi postmilenialisme bersyarat (conditional postmillennialism), yang dipandang lebih sesuai untuk menjadi kerangka eskatologi Pentakosta.